Managing conflict over natural resources in greater Kordofan, Sudan: Some recurrent patterns and governance implications - Siddig, El Fatih Ali; El-Harizi, Khalid; Prato, Bettina (International Food Policy Research Institute, 2007)
Despite the 2005 Comprehensive Peace Agreement, which brought to an end 20 years of civil war in the Sudan, this country continues to experience smaller-scale conflicts, particularly around access to and control of natural resources. Some observers lay the blame for this on ethnopolitical or tribal divisions. However, this paper argues that there are a variety of factors at play behind these conflicts, notably the combination of resource scarcity with a crisis of governance that is particularly evident in transitional areas like the Kordofan region. To gain a sense of the range of conflicts around natural resources in Kordofan, the authors reviewed existing records such as government archives; conducted interviews with politicians, federal and state government officials, farmers, pastoralists, and Native Administration leaders; and investigated findings in the field. Interviews also served to examine people’s knowledge about government natural resource policies and their perceptions of the roles played by government and the Native Administration in conflict management and resolution. The paper presents 20 cases of stalemate competition or open conflict over natural resources in Kordofan. The cases center on (1) conflicts between farmers and herders over stock routes, gum arabic forests, gardens, watering points, and the use of dars (tribal homelands); (2) conflicts between herders and small farmers and government agents or large private investors over mechanized farming areas, oil infrastructure, and other private investments. In their analysis of natural resource governance in Sudan, the authors find that natural resources policies have often been weak foundations for sustainable resource use, and in some cases they have actually contributed to conflict. In addition, the volatile path of government devolution efforts concerning natural resources has undermined governance of these resources. While conflicts between farmers and herders were managed relatively successful in the past through customary land tenure systems, this is less and less the case today as a result of larger herds, reduced water and pasture, instability and prejudices stirred up by the war, and a proliferation of arms among herders. In addition, patron–client politics, weak natural resource management and development policies, and top-down government institutions have encouraged ethnic polarization and social divisions. The authors find that measures are needed to reform the process of natural resource management, making land use planning more comprehensive, building on local livelihood systems, and increasing public spending on infrastructure. In addition, sustainable property rights on farmland and on mobile resources should be redefined, and informal conflict management mechanisms restored to the extent that this is possible.